Aujstamento de redes GPS em conformidade com as exigências da Lei 10.267/2001 - Da Silva, Heloisa Alves [UNESP]; Galera Monico, Joao Francisco [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2009)
In Brazil, there have been several GPS applications and with the introduction of the Law 10.267/2001 that among other dispositions, deals with georeferencing of the rural parcels. However, most commercial softwares of processing and adjustment of GPS data don't let users to evaluate their results in a reliable way. For example, the constraints are normally used as absolute, which provides results with very optimists precisions. The adoption of additional analyses and the implementation of softwares can reduce these kinds of problems. Thus, a software for adjustment of GPS networks was developed, aiming at assisting the requirements of the Law 10.267/2001 in a reliable way. In this context, in this work it is analyzed the adjustments of GPS networks, by using absolute and relative constraints. In the latter, the adjustments were accomplished considering and not considering the correlations among the coordinate positions.
Adjusting GPS networks according to Law 10.267/2001 dispositions
Keywords: Positioning; GPS Network; Stochastic Model